Resilience in Complex Systems: An Agent‐Based Approach. Issue 2 (29th May 2017) - Pumpuni‐Lenss, Gloria; Blackburn, Timothy; Garstenauer, Andreas
ABSTRACT: This paper presents results from a research project on the behavior of complex systems after they experience disruptive events that impact their performance. As systems become more complex, the probability increases that they will exhibit emergent behavior that could lead to system failures or widespread and prolonged service interruptions. A complex adaptive system (CAS) approach is used to conceptualize a complex network system that has been impacted by disruptions and perturbations. A combination of network analysis and agent‐based modeling is used to measure the performance of the system as it responds to disruptive events and restoration efforts. This system‐level behavior is an emergent property of the complex network and represents system resilience. Various resilience measures are used to quantify system resilience and assess the effectiveness of strategies system owners employ to restore the system. We illustrate our techniques by characterizing a critical infrastructure system network as a CAS, and applying an agent‐based simulation with an adaptive algorithm.